Leech’s Meanings in Robert Burns’ Poem “A Red, Red Rose” - Jimmi - - (International Journal of English Linguistics, Literature, and Education (IJELLE), 2022)
Meaning can be revealed with types of meaning. The identification of the meaning is included in the semantic realm. Semantics is a branch of linguistics that deals explicitly with meaning. Disclosure of any meaning contained in a poem is a challenge. There are seven types of meaning proposed by Leech's. Then it can be raised to question what are meanings within the poem "A Red, Red Rose". Descriptive method is applied to reveal the meanings by lyrics. It is found that "A red, red rose" is a great poem that can represent the analysis of types of meaning. There are six types of meaning found, except collocative meaning. Conceptual, social, reflective, affective, thematic, and connotative meanings are the most to the least findings of meaning in this poem, respectively. This research can be used as a model to analyze other poems with the same focus of meaning. With the same reference theory of Leech, or other experts can be implied too.